Efeito da hipertensão renovascular 2R1C sobre as células tronco da medula óssea de camundongos - Campagnaro, Bianca Prandi (2008)
Angiotensin II has been recognized for a long time as a powerful vasoconstrictor. In addition, several studies have attributed a variety of other biological activities to this peptide, such as, cellular growth, proinflammatory and immunomodulator effects. Moreover, high angiotensin II levels increase reactive oxygen species production. Although, some reports show that different cardiovascular diseases affect the number of several bone marrow cell populations, the effect of this peptide on these cells and DNA remains unclear. The objective of this study was to evaluate the effects of 2K1C renovascular hypertension on the number and DNA damage of bone marrow stem cells in mice. Experiments were conducted on male C57 mice (averaging 23 g), which were randomly separated in two groups: Sham (n=10) and two-kidney one-clip (2K1C, n=10). The renovascular 2K1C hypertension was induced by placing a stainless clip around the left renal artery. The Sham group was subjected to the same surgical procedure, without clip placement. Animals were studied 14 days later, when a catheter was inserted into the right carotid artery for direct arterial pressure measurements. Then, the animals were euthanized, bone marrow was flushed out of the tibiae and femurs and the mononuclear cells isolated by density-gradient centrifugation. Cells were counted using a Neubauer chamber. The identification and quantification of different bone marrow cell population were determined by immunofluorescence detection using a mixture of antibodies. Mononuclear cells were stained with CD117-FITC and CD90.2-PE (5μl/106 cells). The hematopoietic and mesenchymal stem cells were quantified by flow cytometry. The level of DNA damage was determined by the Comet Assay. Cell samples were mixed with low melting point agarose, spread on slides precoated with normal melting point agarose and submerged in lysis solution. Then, comet slides were placed on an electrophoresis chamber filled with unwinding alkali buffer electrophoresed, neutralized, fixed, stained with ethidium bromide and visualized in a fluorescence microscope. Data are expressed as means±SEM. Statistical analysis was performed with Student´s t test. *p<0.05. As expected, blood pressure was higher in 2K1C than in Sham mice (Sham: 133±1,5 mmHg vs. 2K1C: 182±12,5 mmHg). Renovascular hypertension did not affect cell viability (Sham: 97%±0.54 vs. 2K1C: 96%±0.54) and monocyte cell number (Sham: 2.81±0.46 vs. 2K1C: 3.32±0.34 cells/ml x 106 ). However, 2K1C mice presented a significant decrease in stem cell number (2.26±0.13 cells/ml x107 ) when compared with Sham (2.66±0.11 cells/ml x107 ) and a simultaneous increase in lymphocyte number (1.98±0.15 vs. 1.22±0.25 cells/ml x106 ), compared with Sham mice. The flow cytometry analysis showed a significant increase in hematopoietic stem cell number in hypertensive mice (0,41±0,16%) when compared with Sham mice (1,75±0,18%). The mesenchymal stem cell number did not show difference between the groups (Sham: 2,36±0,61% vs. 2K1C: 1,48±0,22%). The comet assay showed that 2K1C mice presented high to severe DNA damage, while Sham mice presented none to moderate DNA damage. Our data suggest that angiotensin II-dependent renovascular hypertension reduce stem cell number by the augmentation of asymmetric cell division rate, which leads to an increase of hematopoietic stem cells differentiation. The elevated differentiation rate could be confirmed by the augment of inflammatory cells number produced in bone marrow. In addition, this model of experimental hypertension leads to DNA damage which could be due to augmented reactive oxygen species produced by angiotensin II high levels, which is known to cause genotoxicity by DNA degradation.